Application Of Carrageenan In Making of Skin Lotion - Anna Carolina Erungan; Sri Purwaningsih; Syeni Budi Anita (Department of Aquatic Product Technology IPB University in collaboration with Masyarakat Pengolahan Hasil Perikanan Indonesia (MPHPI), 2009)
The objective of the study is to utilize carrageenan into skin lotion making as a thickener, stabiliser, emulsifier and humectan. The concentration of carrageenan that used were 0%, 1%, 2%, and 3%. Parameter observed were sensory charracteristic, chemical charracteristic, and physic. Skin lotion made from the best carrageenan concentration stored for 30 days in room temperature, and then compared with other skin lotion added with and without setyl alcohol, and also skin lotion without carrageenan. Parameter observed were skin humidity, sensory charracteristic, physical and chemical charracteristic, and also total microbial after 3 months storage. The results showed that skin lotion with 2% carrageenan has the best quality with parameter sensory of panel preferences was from quite likely until most likely, pH 7,5; viscosity 5675 cP, and emulsion stability was 100%, skin humidity value has the highest percentage and showed the lowest decrease of skin humidity compare with product with and without setyl alcohol, and product without carrageenan. Panel preferences decreased during 30 days storage even physical and chemical characteristic were in still good condition, pH product tend to be constant, where viscosity increased. After 3 months storage, total microbial was 1,0 x 10^1 cfu per gram, while the product added with setyl alcohol has no microbial colony. Poduct without setyl alcohol and without carrageenan has 2,0 x 10^1 cfu per gram. The product is safe to use, where total microbial was below standard of SNI 16-4399-1996 that is 1,0 x 10^2 cfu per gram.Keywords: Skin lotion, carrageenan, setyl alcohol, skin humidity, emulsion stability.